The Effect of Jaran Dor Dance Practice on Improving Self – Confidence in Grades IV-VI Students - Alfiyani, Nur; Jumaidi, Susanto; Syawaludin, Muhammad (Program Studi Psikologi Islam, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This study examines the effect of Jaran Dor Dance practice on improving the self-confidence of students in grades IV-VI SDN 1 Tunggorono. Using an experimental approach with a pre-experimental one-group pretest-posttest design, this study involved 30 students who were selected through purposive sampling techniques. Data were collected using a confidence scale in Likert format and supported by observation and documentation. The Jaran Dor Dance intervention is carried out in a structured manner, paying attention to the characteristics of the development of elementary school students and the potential of local cultural arts as a medium for individual capacity development. The results of the analysis showed a significant increase in self-confidence (t = -42.419, p < 0.001) with an average increase of 13.93 points. Observational data revealed that students progressively demonstrated increased willingness to perform in front of peers, showed more active participation in group discussions, and exhibited greater initiative in leading dance movements by the final sessions. These findings indicate that Jaran Dor Dance is effective in increasing students' confidence through culturally meaningful learning experiences.